2020
DOI: 10.1007/s00228-020-03070-0
|View full text |Cite
|
Sign up to set email alerts
|

A real or apparent decrease in glomerular filtration rate in patients using olaparib?

Abstract: Purpose Olaparib is a poly (ADP-ribose) polymerase (PARP) inhibitor indicated for ovarian and metastatic breast cancer. Increased serum creatinine levels have been observed in patients taking olaparib, but the underlying mechanism is unknown. This study aimed to investigate if patients receiving olaparib have increased creatinine levels during olaparib treatment and whether this actually relates to a declined glomerular filtration rate (GFR). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Studies have shown that olaparib likely causes inhibition of renal transporters leading to a reversible, dose-dependent increase in creatinine. 25 Consistently, strong signal strength of blood creatinine increased (PT: 10005483) has also been reported in our analysis. However, some unexpected and significant safety signals related to olaparib on renal function such as glomerular filtration rate decreased (PT: 10018358), renal impairment (PT: 10062237) and hydronephrosis (PT: 10020524) were shown simultaneously based on our results of FAERS data.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that olaparib likely causes inhibition of renal transporters leading to a reversible, dose-dependent increase in creatinine. 25 Consistently, strong signal strength of blood creatinine increased (PT: 10005483) has also been reported in our analysis. However, some unexpected and significant safety signals related to olaparib on renal function such as glomerular filtration rate decreased (PT: 10018358), renal impairment (PT: 10062237) and hydronephrosis (PT: 10020524) were shown simultaneously based on our results of FAERS data.…”
Section: Discussionsupporting
confidence: 91%
“…22,23 One explanation for this observation is that olaparib likely inhibits renal transporters, leading to a reversible and dose-dependent increase in creatinine, and does not affect glomerular filtration rate. 23 One patient on this trial developed AML 3 months after discontinuing olaparib. The incidence of myelodysplastic syndrome (MDS)/AML in patients treated in clinical trials with olaparib monotherapy was 3.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of serum creatinine have been documented in about 10–15% of patients receiving PARP inhibitors ( Table 2 ). These drugs can interfere with several renal transporters, such as MATE1, MATE2-K, OCT1 and OCT-2, determining an increase in serum creatinine without actually affecting kidney function [ 71 , 72 ]. Hence, alternative ways to assess renal function (e.g., radionuclide renal scan) should be considered in case of creatinine elevation before reducing the dose of PARP inhibitor [ 26 , 71 ].…”
Section: Safety Profile Of Ddr-targeting Agentsmentioning
confidence: 99%